Information systems - Baltzan, Paige (McGraw-Hill/Irwin, 2011)
The visual impact of the magazine format will win students over quickly. They'll love the price. And the fascinating, sometimes hard-to-believe real examples will keep them reading. Baltzan and Phillips approach discusses various business initiatives first and how technology supports those initiatives second. The premise for this unique approach is that business initiatives drive technology choices in a corporation. Therefore, every discussion addresses the business needs first and addresses the technology that supports those needs second. This approach takes the difficult and often intangible MIS concepts, brings them down to the student's level, and applies them using a hands-on approach to reinforce the concepts. M: Information Systems provides the foundation that will enable students to achieve excellence in business, whether they major in operations management, manufacturing, sales, marketing, etc. M: Information Systems is designed to give students the ability to understand how information technology can be a point of strength in an organization